Critical Assessment of Current Force Fields. Short Peptide Test Case - Vymětal, Jiří; Vondrášek, Jiří (Journal of chemical theory and computation, 2013)
The applicability of molecular dynamics simulations for studies of protein folding or intrinsically disordered proteins critically depends on quality of energetic functions-force fields. The four popular force fields for biomolecular simulations, CHARMM22/CMAP, AMBER FF03, AMBER FF99SB, and OPLS-AA/L, were compared in prediction of conformational propensities of all common proteinogenic amino acids. The minimalistic model of terminally block amino acids (dipeptides) was chosen for assessment of side chain effects on backbone propensities. The precise metadynamics simulations revealed striking inconsistency of trends in conformational preferences as manifested by investigated force fields for both backbone and side chains. To trace this disapproval between force fields, the two related AMBER force fields were studied more closely. In the cases of FF99SB and FF03, we uncovered that the distinct tends were driven by different charge models. Additionally, the effects of recent correction for side chain torsion (FF99SB-ILDN) were examined on affected amino acids and exposed significant coupling between free energy profiles and propensities of backbone and side chain conformers. These findings have important consequences for further force field development.